Comprehensive Review on Various Gas Hydrate Modelling Techniques: Prospects and Challenges - Sayani, J.K.S. (Springer Science and Business Media B.V., 2021)
Gas hydrates is one the most complex flow assurance problems encountered in pipelines. The gas hydrate formation in pipelines eventually leads to the blockage of pipelines interrupting pipeline operations and affects transmission safety. Over the years, many mitigation techniques are employed to resolve gas hydrate issues in pipelines. But it is equally important to predict the formation and dissociation conditions of the hydrate formation as the experimental investigation is not always viable. So, an accurate prediction modelling approach is required for it. This paper provides a detailed overview of various gas hydrate modelling techniques. Initially, the details about the thermodynamic and kinetic properties of the gas hydrates are discussed. Furthermore, the discussion on the major aspects of the thermodynamic models, Kinetic models, Statistical Models, Models developed using Computational Fluid Dynamics, and Artificial Neural Networks techniques are highlighted. Finally, shortcomings and potential prospects of gas hydrate modelling procedures are addressed. Â© 2021, CIMNE, Barcelona, Spain.